2009
DOI: 10.1002/bit.22560
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of native propionyl‐CoA and methylmalonyl‐CoA metabolism on heterologous polyketide production in Escherichia coli

Abstract: 6-Deoxyerythronolide B (6dEB) is the macrocyclic aglycone precursor of the antibiotic natural product erythromycin. Heterologous production of 6dEB in Escherichia coli was accomplished, in part, by designed over-expression of a native prpE gene (encoding a propionyl-CoA synthetase) and heterologous pcc genes (encoding a propionyl-CoA carboxylase) to supply the needed propionyl-CoA and (2S)-methylmalonyl-CoA biosynthetic substrates. Separate E. coli metabolism includes three enzymes, Sbm (a methylmalonyl-CoA mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 22 publications
6
63
3
Order By: Relevance
“…While in the first report of erythromycin production in E. coli, a yield of only $ 20 mg/L of 6-deoxyerythronolide B (6-dEB) was obtained (Pfeifer et al, 2001). Through engineering and optimization of the 6-dEB biosynthesis pathway, a final titer of over 100 mg/L was obtained in E. coli (Boghigian et al, 2011;Pfeifer et al, 2002;Zhang et al, 2009). Given 6.…”
Section: Discussionmentioning
confidence: 98%
“…While in the first report of erythromycin production in E. coli, a yield of only $ 20 mg/L of 6-deoxyerythronolide B (6-dEB) was obtained (Pfeifer et al, 2001). Through engineering and optimization of the 6-dEB biosynthesis pathway, a final titer of over 100 mg/L was obtained in E. coli (Boghigian et al, 2011;Pfeifer et al, 2002;Zhang et al, 2009). Given 6.…”
Section: Discussionmentioning
confidence: 98%
“…There were also researches concerning products involved Sbm cycle. Zhang et al studied the role of propionyl-CoA and methylmalonyl-CoA metabolism, and found propionyl-CoA could be supplied for polyketide production by E. coli in complex media, but the Sbm cycle might not be directly involved [20]. In the research for propanol production, Sbm cycle was also employed to convert succinyl-CoA to propionyl-CoA.…”
Section: Introductionmentioning
confidence: 99%
“…8 For many assembly-line PKS pathways, the extender unit for the polyketide chain is (2 S )-methylmalonyl-CoA (mmCoA), a metabolite not naturally produced by E. coli. 9 Murli et al 10 compared three routes of heterologous mmCoA production in E. coli : (1) carboxylation of propionyl-CoA by the propionyl-CoA carboxylase (PCC) from Streptomyces coelicolor , (2) conversion of succinyl-CoA to (2 R )-mmCoA and then to (2 S )-mmCoA by the mmCoA mutase/epimerase from Propionibacterium shermanii and (3) synthesis of (2 S )-mmCoA from methylmalonate by the malonyl/methylmalonyl-CoA ligase from S. coelicolor . The 6-dEB titers varied depending on the means of mmCoA production, with the PCC system consistently proving the most productive.…”
Section: Introductionmentioning
confidence: 99%